Effect of depth on shear-wave elastography estimated in the internal and external cervical os during pregnancy - Hernandez-Andrade, Edgar (2014)
AIM: To investigate the effect of depth on cervical shear-wave elastography. METHODS: Shear-wave elastography was applied to estimate the velocity of propagation of the acoustic force impulse (shear-wave) in the cervix of 154 pregnant women at 11-36 weeks of gestation. Shear-wave speed (SWS) was evaluated in cross-sectional views of the internal and external cervical os in five regions of interest: anterior, posterior, lateral right, lateral left, and endocervix. Distance from the center of the US transducer to the center of the each region of interest was registered. RESULTS: In all regions, SWS decreased significantly with gestational age (p=0.006). In the internal os SWS was similar among the anterior, posterior and lateral regions, and lower in the endocervix. In the external os, the endocervix and anterior regions showed similar SWS values, lower than those from the posterior and lateral regions. In the endocervix, these differences remained significant after adjustment for depth, gestational age and cervical length. SWS estimations in all regions of the internal os were higher than those of the external os, suggesting denser tissue. CONCLUSION: Depth from the ultrasound probe to different regions in the cervix did not significantly affect the SWS estimations.